Sport and the city, between urban regeneration and sustainable development - Mara Ladu; Ginevra Balletto; Giuseppe Borruso (TeMA: Journal of Land Use, Mobility and Environment, 2019)
Sport has always played a prominent role in civil society. Although it has been conceived as a strategic political means throughout history, nowadays sport is considered a positive force in achieving sustainable development. The international documents recognize the contributions it makes to health, education and social inclusion objectives.